(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract— The continuation of increasing the power demand in Libya leads to raise the voltage regulation issues especially in distribution networks. This requires integrating more distributed generators (DGs) into distribution networks to meet such demand. However, operating several DGs into distribution networks raises stability, power management and voltage regulation challenges in Libyan power systems. This is due to the confliction of operation between the new integrated DGs and the existing equipments such as On Load Tap Changes Transformers (OLTCT). This paper introduces a potential solution to operate additional DG with existing OLTCT using Power Management System (PMS) supervision to overcome such challenges. The PMS controller works to supervise controllers of existing OLTCT and controllers of Automatic voltage regulator (AVR) and Governor (GOV) for additional DG to avoid the voltage regulation issue and to meet future demand.